2006
DOI: 10.1111/j.1365-2699.2005.01430.x
|View full text |Cite
|
Sign up to set email alerts
|

Local and regional assessments of the impacts of plant invaders on vegetation structure and soil properties of Mediterranean islands

Abstract: Aims Although biological invasions occur throughout the world, and some invaders are widespread in many habitats, few studies on the ecological impact of invaders have examined multiple sites. We tested how the impact of three widespread plant invaders changed depending on the identity of the species and the invaded island. We also tested whether relative species loss was lower in species-rich communities than in species-poor ones.Location We conducted floristic surveys and soil analyses in eight Mediterranean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
232
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(260 citation statements)
references
References 46 publications
15
232
4
5
Order By: Relevance
“…One of the most prominent tree invaders worldwide is A. altissima (also known as Tree-of-Heaven, hereafter Ailanthus), a fast-growing deciduous tree that is particularly aggressive and widespread in temperate and Mediterranean-climate areas (Badalamenti, Barone, Pasta, Sala, & La Mantia, 2012;Meloche & Murphy, 2006;Vilà et al, 2006). The broad use, mainly for ornamental or afforestation purposes, and peculiar eco-physiological and reproductive traits allowed the naturalisation and spread of Ailanthus from its native range -China and north Vietnam -to Europe, USA and many other regions around the world (Kowarik & Säumel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prominent tree invaders worldwide is A. altissima (also known as Tree-of-Heaven, hereafter Ailanthus), a fast-growing deciduous tree that is particularly aggressive and widespread in temperate and Mediterranean-climate areas (Badalamenti, Barone, Pasta, Sala, & La Mantia, 2012;Meloche & Murphy, 2006;Vilà et al, 2006). The broad use, mainly for ornamental or afforestation purposes, and peculiar eco-physiological and reproductive traits allowed the naturalisation and spread of Ailanthus from its native range -China and north Vietnam -to Europe, USA and many other regions around the world (Kowarik & Säumel, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ej., Lloret & al., 2004;Vilà & al., , 2006Hulme & al., 2008b; Bacchetta & al., 2010); sin embargo, son esca-L. Podda & al. sas las contribuciones que consideran el conjunto de la flora exótica de un territorio, comparándola con la flora autóctona y con las floras, tanto exóticas como autóctonas, de áreas pertenecientes a la misma región biogeográfica mediterránea.…”
Section: Introductionunclassified
“…Invasions by alien plants often results in reduced biodiversity (e.g., Pyšek & Pyšek 1995;Vilà et al 2006;Hejda et al 2009;Foggi et al 2011). Brandes (1991) found that stands dominated by B. orientalis contained a smaller number of species than those with low abundance of B. orientalis.…”
Section: Discussionmentioning
confidence: 99%
“…Biological invasions are regarded to be amongst the most important drivers of adverse changes to ecosystems (Parker et al 1999;Mack et al 2000;Vilà et al 2006). Alien invasive species may inflict significant and costly damage to both natural and managed ecosystems (Manchester & Bullock 2000), requiring very expensive control measures (Pimentel 2011).…”
Section: Introductionmentioning
confidence: 99%